Green Marketing and Environmental Knowledge for Green Tourism - Sri Rahayu; Hikmatul Aliyah; Sudarwati Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Green tourism is growing rapidly in various regions in Indonesia, including in East Lampung. The approach in this study uses a green marketing strategy to increase the intention to visit eco-friendly tourist attractions. This study aims to examine the effect of green marketing components, namely green products, green promotions, and green prices on visiting intentions. Also examine the direct and indirect effects of green products on purchase intention through environmental knowledge. The population and sample of this research are visitors to the Kerang Mas Beach tourism object. The sampling technique used was purposive sampling. Primary data was used in this study, with data collection techniques through online questionnaires. Data were analyzed using Structural Equation Modeling, AMOS Program 21 Version. The results showed that green price and green promotion had an effect on purchase intention, but green product had no effect. In addition, environmental knowledge does not have a role as a mediating variable in the effect of green products on purchase intention. Keywords: Green Marketing Component, Environmental Knowledge, Green Tourism, Purchase Intention